Increased overjet is a risk factor for dental trauma in preschool children - Livia Azeredo Alves Antunes; Isa Fin Gomes; Mariane Hemerly Almeida; Erlange Andrade Borges Silva; Jose De Albuquerque Calasans-Maia; Leonardo Santos Antunes (Wolters Kluwer Medknow Publications, 2015)
Context: Traumatic dental injury and malocclusion constitute a public health problem due to their high prevalence. Preventing or detecting such conditions, in any population, is of paramount importance. Aim: Assessing the association of anterior occlusal characteristics and dental trauma in preschool children. Settings and Design: A cross-sectional study was carried out with 2-6-year-old randomly selected by a sample calculation, resulting in 606 subjects Materials and Methods: A questionnaire to collect information about the sample (age, gender, and race) was sent to the children's parents. Two trained and calibrated examiners (Kappa 0.80) evaluated dental trauma according to criteria established by the World Health Organization. The following anterior occlusal characteristics were evaluated: Normal occlusion, anterior open bite, anterior crossbite, increased overjet (categorized as ≥3 mm), and increased overbite (categorized as ≥3 mm). Statistical Analysis Used: The variables associations were assessed (odds ratio, Chi-square test, and logistic regression, P < 0.05) using statistical software (SPSS, version 16.0). Results: Dental trauma was observed in 20.8% and malocclusion in 48.6% of the children. There is an association between malocclusion and dental trauma (P = 0.01). Children with malocclusion have a 64% higher chance of suffering dental trauma. Increased overjet was the type of malocclusion related to a higher rate of tooth fracture (P < 0.01). Subjects with this type of malocclusion suffered tooth fractures three times more often than subjects with other malocclusion types. Conclusions: There was association of dental trauma and malocclusion. Increased overjet was the most common malocclusion related to dental trauma. Preventive strategies are needed to reduce the rate of anterior malocclusion and, consequently, dental trauma in preschool children.